Degradation and recovery processes in semi-arid patchy rangelands of northern Patagonia, Argentina - Kröpfl, A. I. (2013)
Vegetation in many arid and semiarid shrublands is frequently arranged in patches with high plant-cover (shrub patches) interspersed in a low-cover herbaceous matrix (inter-shrub areas). We hypothesized that (a) livestock grazing is an important determinant of such spatial patterns of vegetation, and (b) redistribution of soil resources associated with shrub patches helps in the recovery of vegetation in inter-shrub areas. To test these hypotheses we (a) used line transects to compare spatial variations in vegetation, soil microtopography, and soil physicochemical properties in grazed areas and areas protected from grazing since 1970, (b) added sediment and seeds to inter-shrub areas, and (c) measured resource redistribution after a wildfire. Results were consistent with the hypotheses. They indicated greater spatial heterogeneity in vegetation, soil microtopography and soil physicochemical properties in grazed areas than in protected areas, and that addition of sediment and seeds or redistribution of soil resources from shrub patches after a wildfire enhanced re-establishment of vegetation in degraded inter-shrub areas. As a synthesis, a conceptual model of degradation and recovery processes in semi-arid shrublands of Northern Patagonia is presented.